Respuesta :

Answer:

A-B= (a,b,c,d)-(p,q,r,s)

=( )

B-A =(p,q,r,s)-(a,b,c,d)

( )

Answer:

A - B = { a , b , c , d }

B - A = { p , q , r , s }

Step-by-step explanation:

Given,

A = { a , b , c , d }

B = { p , q , r , s }

Let's find the difference of two set A and B :

A - B = { a , b , c , d } - { p , q , r , s }

The difference of two sets A and B is denoted by A - B and defined as the set of all the elements of A only which are not in B.

A - B = { a , b , c , d }

Now, let's find the difference of two sets B and A

B - A = { p , q , r , s } - { a , b , c , d }

Similarly, The difference of two sets B and A is denoted by B - A and defined as the set of the all elements of set B only which are not in A.

B - A = { p , q , r , s }

Hope I helped!

Best regards!!

ACCESS MORE